Comparative Analysis of the Accuracy Value of Playgo Sales Forecasting Using the Single and Weight Moving Average Method at PT. XYZ - Sulistyo, Suryo; Zahra, Shahla Fathia Az; Soesilo, Rahman; Valentin, Adelia Dwi; Nirfison, Nirfison; Sucipto, Eko Hadi; Fitriyanto, Abdul Rouf (PT FORMOSA CENDEKIA GLOBAL, 2024)
The development of the business world continues to increase along with the large number of requests for products needed, so it is important for companies to create optimal planning strategies, both production planning and demand planning, so that companies are able to achieve their targeted goals. To achieve company goals, one of the company's activities is to carry out forecasting related to the number of sales or consumer demand for the goods or services produced. PT. XYZ is a developing company whose production results are superior and certified educational toys for children. The analysis used in forecasting is a single 2 period and 3 period moving average method as well as a weighted moving average with weightings of 50,20,30 and 50,25,25. The aim of this research is, firstly, to find out the sales forecasting of playgo type children's educational toys and secondly to find out the most accurate sales forecasting method. The research results show that the method with the smallest error value is the Weight Moving Average method with weightings of 50, 20, 30, where the Mean Absolute Error (MAE) value is 570, the Mean Square Error (MSE) is 447,036, and the Mean Absolute Percentage Error (MAPE) of 1.97%.